SPACE OF SOLUTIONS OF LINEAR DIFFERENTIAL EQUATION OF SECOND ORDER AS 2-NORMED SPACE (Balkan Journal of Applied Mathematics and Informatics, 2021)
In [1] is introduced the notion of 2-norm, and in [2] is given an equivalent definition for 2-norm, and with its help the number of axioms is reduced to equal number as in regular norm of vector space. In this paper is given the connection between n-norms and the solutions of differential equation of second order when the solutions are in trigonometric shape in the sense of the solutions of prof. d-r D. Dimitrovski.
Keywords: n-semi norm, 2-subspace, n-linear functional, differential equation of second order, solution of DE